Yeast frataxin is stabilized by low salt concentrations: cold denaturation disentangles ionic strength effects from specific interactions. - Domenico Sanfelice; Rita Puglisi; Stephen R Martin; Lorenzo Di Bari; Annalisa Pastore; Piero Andrea Temussi (PLoS ONE)
Frataxins are a family of metal binding proteins associated with the human Friedreich's ataxia disease. Here, we have addressed the effect of non-specifically binding salts on the stability of the yeast ortholog Yfh1. This protein is a sensitive model since its stability is strongly dependent on the environment, in particular on ionic strength. Yfh1 also offers the unique advantage that its cold denaturation can be observed above the freezing point of water, thus allowing the facile construction of the whole protein stability curve and hence the measurement of accurate thermodynamic parameters for unfolding. We systematically measured the effect of several cations and, as a control, of different anions. We show that, while strongly susceptible to ionic strength, as it would be in the cellular environment, Yfh1 stability is sensitive not only to divalent cations, which bind specifically, but also to monovalent cations. We pinpoint the structural bases of the stability and hypothesize that the destabilization induced by an unusual cluster of negatively charged residues favours the entrance of water molecules into the hydrophobic core, consistent with the generally accepted mechanism of cold denaturation.